Clonagem humana: aspectos éticos - Muñoz, Daniel Romero (2004)
Moral dilemmas have greatly increased since the birth of Dolly, the clone sheep, and those led to an unreasoned and misinformed argumentations to prohibit this kind of research in many countries. In this article the author examines the reasons of those dilemmas in the light of bioethics and the update knowledge, emphasizing that the best politics is not the prohibition but the control of freedom research. Particular attention is paid to the question of the that in Brazil there is mechanism that would be used to get this kind of research under control, but effort is necessary to developing of ethical sense, mainly, of the future researchers.